The Influence of Regional Tax Revenue, and Regional Retribution, on Direct Expenditure of the Regional Government of East Lombok Regency for the 2016-2020 Fiscal Year - Isnawati, Isnawati (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to determine the effect of regional tax revenues and regional levies on direct expenditure by the regional government of East Lombok Regency for the 2016-2020 fiscal year. This study aims to determine the effect of regional tax and retribution revenues on regional direct expenditure in East Lombok Regency. The analytical method used in this study is the quantitative method. Based on the results of the analysis of regional tax variables on the Regional Direct Expenditures variable, it has a tcount of 3.013 (tcount > ttable, namely 2.446) and a significance value of 0.017 (sig. <0.05). This means that H0 is rejected and Ha is accepted or it can be concluded that local tax revenues have a positive and significant influence on direct spending. Based on the results of the analysis on the Regional Retribution variable on the Regional Direct Expenditures variable, it has a tcount of 3,513 (tcount > ttable, namely 2,446) and a significance value of 0.008 (sig. <0.05). The conclusion of this study is that regional fees have a positive and significant influence on direct spending.